3D and 2D left ventricular systolic function imaging - from ejection fraction to deformation. Cardiac resynchronization therapy - substudy - Szulik, Mariola; ŒLiwiñska, Anna; Lenarczyk, Radoslaw; Szyma£A, Magdalena; Kalinowski, Mariusz E.; Markowicz-Pawlus, Ewa; Kalarus, Zbigniew; Kukulski, Tomasz (Acta Cardiologica, 2015)
Introduction 3D echocardiography off ers options of left ventricular systolic function analysis. The aims of this study are: to assess the usefulness of 3D echocardiography, to test 3D regional measurements (with area strain) among a spectrum of patients and then to check prospectively the value of 3D echocardiography vs 2D in the assessment of response to resynchronization. Methods The fi rst retrospective study group comprises 42 subjects: 23 consecutive patients with left ventricular systolic heart failure and 19 healthy control subjects. The left ventricle was assessed by: 2D-Simpson's biplane, 3D-triplane and -automated volumetric method. Next, 24 patients undergoing cardiac resynchronization therapy were prospectively assessed before and after 6 months. A haemodynamic response criterion of 15% left ventricular end-systolic volume (ESV) reduction was used. Results The 3D volumetric method was the fastest method for left ventricular ejection fraction assessment (bi-33 vs tri-53 vs145 sec, ANOVA P< 0.001). In heart failure the only strain parameter associated with QRS width was global peak longitudinal strain (r = 0.47, P= 0.023). A high agreement in left ventricular ejection fraction and volumes between methods was observed. The following measures select resynchronization candidates in the heart failure group: (1) 3D global longitudinal strain (AUC-0.756; P= 0.022; the cut-off value > -9.52%; 78% sensitivity, 80% specifi city), radial strain (AUC-0.739; P= 0.086; cut-off value ≤ 20%; 78% sensitivity, 80% specifi city) and area strain (AUC-0.733; P= 0.045; cut-off value > -13.5%; 67% sensitivity, 80% specifi city). The agreement between the response assessment by Simpson's biplane and 3D was 78% with a negative predictive value of 100%. The lack of global area strain improvement after cardiac resynchronization therapy has a negative predictive value of 100% in the selection of non-responders. Conclusions 3D echocardiography is applicable in the assessment of both preserved and reduced left ventricular ejection fraction. This assessment is fast and requires minimal user intervention. 3D strain may help in cardiac resynchronization therapy candidates and response assessment. After cardiac resynchronization, none of the patients were incorrectly identifi ed as responder to cardiac resynchronization therapy by 3D algorithms compared to 2D Simpson's reference.